How to Measure the Green Façade Sustainability? A Proposal of a Technical Standard. (September 2016) - Tedesco, Silvia; Giordano, Roberto; Montacchini, Elena
Abstract: Different guidelines drive EU countries to use greening systems – green roofs and green façades - as a sustainable strategy to maximize environmental buildings performance. While technical standards concerning green roofs are available, standards concerning green façades and particularly Living Wall Systems (LWSs) still missing. The paper deals with a research carried out in order to develop a proposal of a technical standard to be adopted as method and tool to measure the performances of green façades and LWSs according to a sustainable approach. The proposal was implemented in consistency to an Italian standard (UNI 11235:2015). The UNI 11235 contains the instructions for designing, building up, monitoring and maintaining the green roofs. Although the standard is not international some basic information may be applied at global scale and most importantly at green façades. The study was focused to setting-up a proper number of requirements to be met in: designing a LWS; defining guidelines for construction stage; monitoring the performance. Requirements and guidelines were set up according to a wide study on international references and thanks to an industrial research project where the authors were involved. Monitoring carried out on chamber tests and on-site was enabled to getting comprehensive data helpful for assessing environmental properties of LWSs and on the whole to characterizing some requirements to be used in the standard.